2000
DOI: 10.4049/jimmunol.165.6.3145
|View full text |Cite
|
Sign up to set email alerts
|

An Intra-Peyer’s Patch Gene Transfer Model for Studying Mucosal Tolerance: Distinct Roles of B7 and IL-12 in Mucosal T Cell Tolerance

Abstract: Development of mucosal immunity and tolerance requires coordinated expression of a number of genes within the mucosa-associated lymphoid tissue (MALT). To study the roles of these genes in the MALT, we have established a MALT-specific gene transfer model using replication-defective adenovirus as vector. In this model, the target gene of interest is directly delivered into the Peyer’s patch by intra-Peyer’s patch injection of the recombinant virus. Using this gene transfer model, we investigated the roles of B7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 63 publications
1
17
0
Order By: Relevance
“…Within the Peyer's patches, macrophages and epithelial cells were transgene positive, whereas T-and B lymphocytes were not transduced. 51 This is consistent with the observation that lymphocytes are only poorly receptive to adenovirus infection, because they express only low levels of coxsackie and adenovirus receptor (CAR) for virus attachment through the fibre capsid protein and display only small amounts of av-integrins required for interaction with penton-base proteins and virus internalization. 52,53 Interestingly, studies in mice with experimental colitis as a model for human IBD showed that disruption of intestinal epithelial integrity and other histopathological alterations during mucosal inflammation increased transduction of lamina propria mononuclear cells (LPMC) by adenoviral vectors.…”
Section: Gene Transfer Approaches In Ibd S Wirtz and Mf Neurathsupporting
confidence: 88%
See 1 more Smart Citation
“…Within the Peyer's patches, macrophages and epithelial cells were transgene positive, whereas T-and B lymphocytes were not transduced. 51 This is consistent with the observation that lymphocytes are only poorly receptive to adenovirus infection, because they express only low levels of coxsackie and adenovirus receptor (CAR) for virus attachment through the fibre capsid protein and display only small amounts of av-integrins required for interaction with penton-base proteins and virus internalization. 52,53 Interestingly, studies in mice with experimental colitis as a model for human IBD showed that disruption of intestinal epithelial integrity and other histopathological alterations during mucosal inflammation increased transduction of lamina propria mononuclear cells (LPMC) by adenoviral vectors.…”
Section: Gene Transfer Approaches In Ibd S Wirtz and Mf Neurathsupporting
confidence: 88%
“…Chen et al 51 reported successful gene transfer into the Peyer's patches by direct injection of recombinant Ad5. Within the Peyer's patches, macrophages and epithelial cells were transgene positive, whereas T-and B lymphocytes were not transduced.…”
Section: Gene Transfer Approaches In Ibd S Wirtz and Mf Neurathmentioning
confidence: 99%
“…In the mouse intestine, this population of Tr cells has been shown to constitutively express CTLA-4 and is able to control intestinal inflammation (22). Crosslinking of CTLA-4 (resulting in CTLA-4 signaling) can induce TGF-␤ production by murine CD4 ϩ T cells (23) and the suppressive effect of these Tr cells has been demonstrated to be TGF-␤ dependent (22). The disruption of Tr cell function by anti-CTLA-4 treatment may have played an important role in the increased immune responses against peanut allergens that were observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…CD4 ϩ T cells, especially after CD28 cross-linking, also express high levels of CD40 ligand, which interacts with CD40 expressed on APC to promote IL-12 secretion (36) and B7 expression. Furthermore, IL-12 may act synergistically with B7.1 to abrogate mucosal T cell tolerance and to induce intestinal inflammation (48). According to recent report (49), this priming occurs in regional Ag-draining lymph nodes and will be followed by homing of the Ag-primed cells to the lamina propria of the gut.…”
Section: Discussionmentioning
confidence: 99%